Nearly Primary-2-Absorbing Submodules and other Related Concepts - Sh. Ajeel, Ali; A. Abdulla, Omar; K. Mohammadali, Haibat (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
Our aim in this paper is to introduce the notation of nearly primary-2-absorbing submodule as generalization of 2-absorbing submodule where a proper submodule of an -module is called nearly primary-2-absorbing submodule if whenever , for , , , implies that either or or . We got many basic, properties, examples and characterizations of this concept. Furthermore, characterizations of nearly primary-2-absorbing submodules in some classes of modules were inserted. Moreover, the behavior of nearly primary-2-absorbing submodule under -epimorphism was studied.